2022
DOI: 10.3390/mi13060833
|View full text |Cite
|
Sign up to set email alerts
|

Automated Open-Hardware Multiwell Imaging Station for Microorganisms Observation

Abstract: Bright field microscopes are particularly useful tools for biologists for cell and tissue observation, phenotyping, cell counting, and so on. Direct cell observation provides a wealth of information on cells’ nature and physiological condition. Microscopic analyses are, however, time-consuming and usually not easy to parallelize. We describe the fabrication of a stand-alone microscope able to automatically collect samples with 3D printed pumps, and capture images at up to 50× optical magnification with a digit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Other than that, digital cameras with macro lenses are used in custom setups [16]- [18], or microscopes are equipped with cameras. In other fields, different designs for low-cost open-source and Do It Yourself (DIY) microscopes for different applications have already been developed [19]- [23]. For example, DIY microscopes were proposed for the specific detection of C. elegans nematodes -a widely distributed model organism in developmental biology and genetics [20] or for fluorescence microscopy of 3D cell cultures [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other than that, digital cameras with macro lenses are used in custom setups [16]- [18], or microscopes are equipped with cameras. In other fields, different designs for low-cost open-source and Do It Yourself (DIY) microscopes for different applications have already been developed [19]- [23]. For example, DIY microscopes were proposed for the specific detection of C. elegans nematodes -a widely distributed model organism in developmental biology and genetics [20] or for fluorescence microscopy of 3D cell cultures [21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, DIY microscopes were proposed for the specific detection of C. elegans nematodes -a widely distributed model organism in developmental biology and genetics [20] or for fluorescence microscopy of 3D cell cultures [21]. Other open-source microscopes have been designed for automated observation of bacterial cultures [22], [23]. However, it is noticeable that the majority of open-source microscopes developed are compound microscopes while dissecting microscopes have received little attention to date [24]- [26].…”
Section: Introductionmentioning
confidence: 99%
“…The research findings reported in the 3D-Printed Actuators Special Issue show promising approaches for engineering biology-like actuation. These findings have led to the following: the creation of an anatomically correct robotic hand with human-like grasping capabilities [ 1 ]; emulation of an antagonistic variable stiffness actuation observed in the musculoskeletal system of snakes [ 2 ]; reducing friction in rotating parts and joints by combining 3D printing and radiation pressure [ 3 ]; fabrication of flexible piezoelectric composite actuators without application of any adhesives [ 4 ]; extension of the service life of actuators through geometric and material optimization [ 5 ]; and acceleration of print inspection through an open-source low-power computer-vision hardware [ 6 ].…”
mentioning
confidence: 99%